Mindfulness as a therapeutic tool for adolescents with ADHD - MOSHE, VARDA (E-Journal VFU, 2024)
Mindfulness-based interventions (MBIs) have emerged as promising therapeutic approaches for adolescents with attention deficit hyperactivity disorder (ADHD). This article reviews and synthesizes recent studies on the efficacy of MBIs in improving ADHD symptoms, executive functioning, emotional regulation, and behavioral outcomes among adolescents. Studies by Schonert-Reichl & Stewart-Lawlor (2010), Santonastaso et al. (2020), and Barranco-Ruiz et al. (2019) highlight significant improvements across these domains following various mindfulness interventions, including mindfulness meditation and mindfulness-oriented meditation (MOM) training. Meta-analyses conducted by Lee et al. (2022) and Chimiklis et al. (2018) underscore the consistent positive effects of MBIs on ADHD symptoms and broader functional outcomes. However, findings from Robe & Dobrean (2023) caution that single-session interventions may not yield substantial cognitive performance improvements, suggesting a need for further exploration into intervention duration and intensity. Tercelli & Ferreira (2019) emphasize the importance of sustained mindfulness practice beyond intervention periods for maintaining long-term benefits. Future research directions include optimizing intervention design, exploring technological integration, and integrating mindfulness into educational settings to enhance treatment efficacy and sustainability.
Keywords: emotional regulation; executive functioning; adolescents; ADHD; mindfulness-based interventions